HUMAN CAPITAL AND ITS INFLUENCE ON ECONOMIC DEVELOPMENT. - MICULESCU ANDRA; MONICA BOLDEA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2015)
The present paper had as starting point the idea according to which human capital and investment in human capital, and respectively investment in education, can be considered key determinant of economic growth and development. Our paper draws attention to the conditions necessary so that the effects of education on human capital development and economic development should record maximum values. The paper emphasizes the idea that investments in education become ineffective unless accompanied by a suitable and appropriate strategy for economic and social development, based on socio-economic and political stability, and by the existence of a direct relationship between income, occupation and level of education and professional training. Our analysis also involves the concepts of social capital and psychological capital, both being considered as influencing development theory, practice and policy; although they bring about less clear and direct results, these two forms of capital are considered to improve the economic activity background in a way similar to technical infrastructure; social capital influences the quality of education and health, facilitates access of individuals to markets, supports complex operations and enables the activities’ long-term planning. The paper draws attention to the multidimensional character of the economic development, considering that economic development can therefore express all quantitative, qualitative and structural transformations occurring both within economic processes and along scientific research and manufacturing technologies, in the mechanisms regarding the operation of the economy, namely thinking patterns and the behavior of individuals. On the other hand, the New Economy is described synonymous with a knowledge economy in the broader context of the knowledge society - considering the knowledge based economy, knowledge representing an important factor in determining economic growth.